Communication from the Governor of Virginia concerning the organization of reserved force : January 25, 1864 (Document (Virginia. General Assembly. Senate) ;, 1864)
January 25, 1864 Communication of Governor William Smith to the General Assembly regarding the organization of the reserved force of the state, to be called the "State guard", in recognition of the "formidable enemy" who was marching toward the state.